2012
DOI: 10.2478/s11687-012-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Regression of alveolar echinococcosis after chronic viral hepatitis C treatment with pegylated interferon alpha 2a

Abstract: We present a case of 53 years old patient with transplanted kidney, chronic hepatitis C and alveolar echinococcosis who was treated with pegylated interferon α which resulted in regression and calcification of Echinococcus multilocularis loculi. Patient had been diagnosed with chronic hepatitis C two years after kidney transplantation. Hepatitis was left untreated because of immunosuppressive treatment and satisfactory graft function. Nine years after transplantation the patient was diagnosed with alveolar ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This general picture is supported by previous studies which compellingly showed that the resistance of murine [11] [13] or human [14] , [15] hosts to E. multilocularis metacestodes is associated with a Th1-dominated immune response whereas a Th2-dominated immune response occurs as E. multilocularis metacestodes thrive in these murine [16] , [17] or human [15] , [18] , [19] hosts. In agreement with a parasitocidal role for Th1 responses during AE, administration of Th1-inducing immune-stimulants like Bacillus Calmette–Guérin (BCG) [20] [23] , IL-12 [13] , IFN-α-2a [11] , [24] and IFN-γ [25] , [26] have all been shown to restrain parasite establishment, proliferation or dissemination in rodents experimentally infected with E. multilocularis larvae. Conversely, Th2-dominated immune responses have been tightly associated with progressive forms of AE both in humans [15] , [19] and mice [16] , [17] with compelling evidence pointing at an underlying expansion of regulatory T-cells [27] , [28] .…”
Section: Introductionmentioning
confidence: 84%
“…This general picture is supported by previous studies which compellingly showed that the resistance of murine [11] [13] or human [14] , [15] hosts to E. multilocularis metacestodes is associated with a Th1-dominated immune response whereas a Th2-dominated immune response occurs as E. multilocularis metacestodes thrive in these murine [16] , [17] or human [15] , [18] , [19] hosts. In agreement with a parasitocidal role for Th1 responses during AE, administration of Th1-inducing immune-stimulants like Bacillus Calmette–Guérin (BCG) [20] [23] , IL-12 [13] , IFN-α-2a [11] , [24] and IFN-γ [25] , [26] have all been shown to restrain parasite establishment, proliferation or dissemination in rodents experimentally infected with E. multilocularis larvae. Conversely, Th2-dominated immune responses have been tightly associated with progressive forms of AE both in humans [15] , [19] and mice [16] , [17] with compelling evidence pointing at an underlying expansion of regulatory T-cells [27] , [28] .…”
Section: Introductionmentioning
confidence: 84%
“…In human medicine, infection with three species of tapeworm presents a significant health problem: E. granulosus, with dogs and some other canids as definitive hosts and humans, sheep, goats, cattle, pigs and horses as intermediate hosts and carriers of larval stage (Markell et al, 2000). Other form is alveolar echinococcosis caused by E. multilocularis, with foxes, dogs and catsas definive hosts, small rodents as intermediate hosts and humans as intermediate (accidental) hosts (Dražilová et al, 2012) These two forms are of special importance due to wide distribution and serious medical and economic impact. Third form, polycystic echinococcosis caused mainly by E. vogeli, with bush dogs and dogs as definitive hosts, rodents as intermediate hosts and man and other mammals as accidental hosts is less frequent and restricted to Central and South America (Neva et al, 1994.;Garcia, 2007).…”
Section: Introductionmentioning
confidence: 99%